2020
DOI: 10.1002/bem.22309
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Cell Membrane Potential and Intracellular Protein Transport by High Magnetic Fields

Abstract: To explore cellular responses to high magnetic fields (HMF), we present a model of the interactions of cells with a homogeneous HMF that accounts for the magnetic force exerted on paramagnetic/ diamagnetic species. There are various chemical species inside a living cell, many of which may have large concentration gradients. Thus, when an HMF is applied to a cell, the concentrationgradient magnetic forces act on paramagnetic or diamagnetic species and can either assist or oppose large particle movement through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…It was reported that neurons in the hypothalamic structures can be activated by osmotic stimulation 34 . A high SMF can produce a pressure on the cell membrane due to the concentration‐gradient magnetic forces exerted on paramagnetic/diamagnetic species 35 . We call this pressure as magnetic pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that neurons in the hypothalamic structures can be activated by osmotic stimulation 34 . A high SMF can produce a pressure on the cell membrane due to the concentration‐gradient magnetic forces exerted on paramagnetic/diamagnetic species 35 . We call this pressure as magnetic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…34 A high SMF can produce a pressure on the cell membrane due to the concentration-gradient magnetic forces exerted on paramagnetic/diamagnetic species. 35 We call this pressure as magnetic pressure. In a high enough SMF, the magnetic pressure may cause an imbalance in the osmotic and hydrostatic pressures, which in turn changes the fluxes of ions transported through the cell membrane and the osmotic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…70,71 Therefore, the membrane potential act as the driving force for a large set of secondary transporters, including symporter, antiporter, and uniporter, enabling them to transport substrates against their concentration gradients. 72 In general, the cotransport of PAHs is likely propelled by an electrochemical potential gradient for H + across the membrane, which is established and sustained by PM-bound ATPase. These processes, along with the activity of PAH/H + symporter, were confirmed through various examinations, including observations of medium alkalinization during PAHs uptake, membrane transient depolarization in response to PAH supply, PAHs inhibition uptake by metabolic and ATPase inhibitors such as vanadate and 2,4-dinitrophenol, and PAHs uptake stimulation by low external pH.…”
Section: Uptake and Translocation And The Fate Of Pahs In Plantsmentioning
confidence: 99%
“…Let us start with a brief description of the relevant magnetic forces that may affect diffusion in cells. When a static magnetic field is applied to cell systems, three types of magnetic forces can act on subcellular components, molecules, and ions: (i) the Lorentz force, F L = q[ vB ] (where B is the magnetic induction, q is the ion electric charge, and v is its velocity); (ii) the magnetic gradient force, F ∇ B ∝∇ B 2 [ 23 , 24 , 25 ] (when the magnetic field is uniform (∇ B = 0), the magnetic gradient force is zero); (iii) the concentration-gradient magnetic force, F ∇ n ∝ B 2 ∇ n [ 26 , 27 , 28 , 29 , 30 ] (where ∇ n is the gradient of the concentration of diamagnetic and paramagnetic species, and ∇ is the differential operator nabla).…”
Section: Introductionmentioning
confidence: 99%